Correlations and path analysis for fruit yield in pepper lines (Capsicum chinense L.) - Soares, Renato Silva; Silva, Hellismar Wakson da; Candido, Willame dos Santos; Vale, Luís Sérgio Rodrigues (Comunicata Scientiae, 2018)
Information regarding the correlation between characters are of great importance to simultaneous traits selection in breeding programs. However, quantification and interpretation of the correlations magnitude do not imply in direct and indirect effects. In this context, the path analysis is presented as an alternative and viable tool for the selection process. The objective of this study was to evaluate the phenotypic, genotypic and environmental correlations between eight major agronomic characters in pepper lines (C. chinense L.) and its consequences in direct and indirect effects by path analysis. Eight agronomic traits were assessed under field conditions in 22 C. chinense L lines. According to the results, there is a genetic variability among the evaluated lines, whose yield per plant (PY) and total number of fruits (NF) variables are highly correlated with high direct effect on pepper lines yield. The selection of pepper lines with high yield can be accomplished through direct selection or using a suitable selection index, being advantageous to select lines with other characteristics, such as appropriate scion height and diameter for conducting manual and mechanized harvesting. The use of the constant k is efficient to reduce the variance of path coefficients, providing better estimation of the effects that affects yield.